BODY MASS INDEX AS A DETERMINANT OF OUTCOME OF TREATMENT WITH NON-INVASIVE VENTILATION IN PATIENTS WITH RESPIRATORY FAILURE DUE TO ACUTE EXACERBATION OF CHRONIC OBSTRUCTIVE PULMONARY DISEASE - Pejkovska, Sava; Jovkovska Kaeva, B; Goseva Z; Arsovski, Zoran; Arbutina S (Macedonian Association of Anatomists and Morphologists, 2015)
Introduction: In the last two decades noninvasive ventilation (NIV) has become an integral part of the protocol for the treatment of patients with acute respiratory failure. Aim of the study: To assess the relationship between body mass index (BMI) and outcome of treatment with NIV in patients with acute exacerbation of chronic obstructive pulmonary disease (AECOPD). Material and methods: A total of 52 patients, over the age of 40, hospitalized because of acute exacerbation of COPD and treated with NIV were prospectively recruited. The patients were divided into two groups: 1) successful NIV treatment group; 2) failed NIV treatment group. Results: There was no significant difference in distribution between the two patients groups in terms of sex and age. Compared to group 1, in the group 2, difference was observed in the values of GCS that were lower, and the PaCO2 and APACHE II scores were higher, but the difference between the two groups was not significant (p> 0.05). Significant difference was observed between the values of pH (p <0.05) and BMI (p <0.01). The majority of patients with NIV treatment failure were with BMI <22kg / m2. Conclusion: The degree of acidosis and BMI are factors of statistical significance for the outcome of NIV treatment. Further studies are needed to clarify the reasons for the association between NIV and low BMI.
Keywords: body mass index; COPD exacerbation; noninvasive ventilation; respiratory failure